FMS-like Tyrosine Kinase 1 and Other Associated Factors to Predict in Vitro Fertilization (IVF) Outcomes in Different Causes of Infertility - Mohammed, Lubna S.; Haddad, Namir I.A. (Iraqi Journal of Science, 2024)
As infertility became a significant public health problem, assisted reproductive technologies (ART) were introduced. The study aims to investigate infertility in women undergoing their IVF cycle, the role of FMS like Tyrosine kinase 1, and other associated factors causing infertility, as well as the relationship between FMS like Tyrosine kinase 1 and the IVF outcome. The study population consisted of 136 infertile women who sought medical help at Kamal Al-Samarra'ay Specialized Hospital for infertility treatment. The collection of data was performed by means of a specifically designed questionnaire, which, apart from the demographic data, included questions concerning the causes of infertility. According to the reasons for infertility, the patients who participated in our research were classified into five groups. The study showed that, by comparing the groups, the success rate of IVF was the highest when the causes of infertility were male factor, unexplained, mixed, PCO, and tubal factor. Additionally, the study showed a significant difference (p<0.05) in the level of FMS-like Tyrosine kinase 1, number of embryos, repeated IVF cycles, and embryo transfer (E.T.) between infertility groups. Our study concluded that the clinical parameters were closely associated with IVF outcomes, which could provide information for future clinical interventions to increase successful rates. Our research revealed that FMS-like Tyrosine Kinase 1 has a role in infertility; the greater the value, the higher the success rate. Furthermore, the findings show that there is a close association between FMS-like Tyrosine kinase 1 level and IVF success, and it can be used as a valuable marker to confirm the extent of IVF failure or success.